Pemanfaatan Artificial Intelligence untuk Mendukung Administrasi dan Promosi Kegiatan PKK - Nidya Fitri (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Digital transformation and the rapid development of generative Artificial Intelligence (AI) present significant opportunities for community organizations, including the Family Welfare and Empowerment Movement (Pemberdayaan dan Kesejahteraan Keluarga—PKK), to improve the effectiveness of organizational administration and activity promotion. However, PKK members continue to face challenges in manually preparing administrative documents, have limited skills in creating engaging digital promotional content, and possess insufficient understanding of the ethical and responsible use of AI. This community service program aims to enhance the digital literacy and capacity of PKK members in utilizing AI to support organizational administration, including the preparation of official correspondence, proposals, reports, and meeting minutes, as well as the promotion of organizational activities and products from the Family Income Improvement Program (Usaha Peningkatan Pendapatan Keluarga—UP2K). The program employs a Participatory Learning and Action (PLA) approach consisting of four stages: preparation, training, practice and mentoring, and monitoring and evaluation. Data are analyzed using descriptive statistics for the pre-test, post-test, and participant satisfaction questionnaire, while qualitative descriptive analysis is applied to observational and interview data. The program is expected to increase participants' understanding by at least 30% compared with their pre-training level, enable at least 80% of participants to independently prepare administrative documents and promotional content using AI, and achieve a partner satisfaction rate of at least 85%. The program outputs include a training module, an AI prompt guide, tutorial videos, AI-assisted administrative and promotional templates, and a sustainable digital mentoring community to support the long-term digital transformation of PKK organizations.